Early cardiac remodeling in aortic coarctation: insights from fetal and neonatal functional and structural assessment. (12th November 2020) - Soveral, I.; Crispi, F.; Walter, C.; Guirado, L.; García‐Cañadilla, P.; Cook, A.; Bonnin, A.; Dejea, H.; Rovira‐Zurriaga, C.; Sánchez de Toledo, J.; Gratacós, E.; Martínez, J. M.; et al.
ABSTRACT: Objectives: Coarctation of the aorta (CoA) is associated with left ventricular (LV) dysfunction in neonates and adults. Cardiac structure and function in fetal CoA and cardiac adaptation to early neonatal life have not been described. We aimed to investigate the presence of cardiovascular structural remodeling and dysfunction in fetuses with CoA and their early postnatal cardiac adaptation. Methods: This was a prospective observational case–control study, conducted between 2011 and 2018 in a single tertiary referral center, of fetuses with CoA and gestational age‐matched normal controls. All fetuses/neonates underwent comprehensive echocardiographic evaluation in the third trimester of pregnancy and after birth. Additionally, myocardial microstructure was assessed in one fetal and one neonatal CoA‐affected heart specimen, using synchrotron radiation‐based X‐ray phase‐contrast microcomputed tomography and histology, respectively. Results: We included 30 fetuses with CoA and 60 gestational age‐matched controls. Of these, 20 CoA neonates and 44 controls were also evaluated postnatally. Fetuses with CoA showed significant left‐to‐right volume redistribution, with right ventricular (RV) size and output dominance and significant geometry alterations with an abnormally elongated LV, compared with controls (LV midventricular sphericity index (median (interquartile range; IQR), 2.4 (2.0–2.7) vs 1.8 (1.7–2.0); P < 0.001). Biventricular function was preserved and no ventricular hypertrophy was observed. Synchrotron tomography and histological assessment revealed normal myocyte organization in the fetal and neonatal specimens, respectively. Postnatally, the LV in CoA cases showed prompt remodeling, becoming more globular (LV midventricular sphericity index (mean ± SD), 1.5 ± 0.3 in CoA vs 1.8 ± 0.2 in controls; P < 0.001) with preserved systolic and normalized output, but altered diastolic, parameters compared with controls (LV inflow peak velocity in early diastole (mean ± SD), 97.8 ± 14.5 vs 56.5 ± 12.9 cm/s; LV inflow peak velocity in atrial contraction (median (IQR), 70.5 (60.1–84.9) vs 47.0 (43.0–55.0) cm/s; LV peak myocardial velocity in atrial contraction (mean ± SD), 5.1 ± 2.6 vs 6.3 ± 2.2 cm/s; P < 0.05). The neonatal RV showed increased longitudinal function in the presence of a patent arterial duct. Conclusions: Our results suggest unique fetal cardiac remodeling in CoA, in which the LV stays smaller from the decreased growth stimulus of reduced volume load. Postnatally, the LV is acutely volume‐loaded, resulting in an overall geometry change with higher filling velocities and preserved systolic function. These findings improve our understanding of the evolution of CoA from fetal to neonatal life. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd.